2017
DOI: 10.21577/0103-5053.20170191
|View full text |Cite
|
Sign up to set email alerts
|

HR-MAS NMR Allied to Chemometric on Hancornia speciosa Varieties Differentiation

Abstract: This work describes the potential of chemometric analyses applied to 1 H high-resolution magic angle spinning nuclear magnetic resonance ( 1 H HR-MAS NMR) data for the chemotaxonomic investigation of Hancornia speciosa (Apocynaceae) varieties. This plant, popularly known as mangaba, has a complex morphological differentiation and thus chemical analyses can be used for their taxonomic classification. In comparison to traditional techniques, 1 H HR-MAS NMR allied with chemometrics provided a simple and low cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…pubescens generally clustered together. Other studies using chemometric analyses showed that H. speciosa var speciosa differs from other varieties (Flores et al 2017). Our phylogenetic analysis shows correlation with morphological descriptions suggested by Monachino (1945), in which the varieties H. speciosa var.…”
Section: H Speciosa Varieties Relationshipssupporting
confidence: 87%
See 1 more Smart Citation
“…pubescens generally clustered together. Other studies using chemometric analyses showed that H. speciosa var speciosa differs from other varieties (Flores et al 2017). Our phylogenetic analysis shows correlation with morphological descriptions suggested by Monachino (1945), in which the varieties H. speciosa var.…”
Section: H Speciosa Varieties Relationshipssupporting
confidence: 87%
“…(Monachino, 1945). The identi cation of these botanical varieties is based in the morphological characters; however, the origin of the genetic relationships and the putative hybrids of the botanical varieties is not clear (Collevatii et al 2016;Flores et al 2017). The botanical varieties are dispersed in the Atlantic Rain forest, Cerrado and Caatinga domains, of which the differences among biomes is suitable for phylogeographic and phylogenetic studies, which may be useful to understand of the genetic diversi cation of H speciosa.…”
Section: Introductionmentioning
confidence: 99%
“…Controlled pollination experiment demonstrated that the species is self-incompatible (Darrault and Schlidwein 2005) that was corroborated by pollen dispersal study (Collevatti et al 2016). Some works have shown the existence of genetic variability among and/or within botanical varieties based on quantitative traits (Ganga et al 2009), allozymes (Martins et al 2012), DNA molecular markers (Moura et al 2005, Silva et al 2011, Rodrigues et al 2015, Collevatti et al 2016, Costa et al 2017) and chemical components (Flores et al 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, it has been especially used in the analysis of foodstuffs, such as the identification of lipids, carbohydrates, and small metabolites . This technique has several advantages in metabolomic studies, as it permits plant genotypes to be differentiated such as genetically modified organisms, different phenotypes, and chemotaxonomy identification . HR‐MAS NMR is also widely used for quality control, such as determining the purity, authenticity, and origin of several plant‐based products …”
Section: Introductionmentioning
confidence: 99%
“…3,[7][8][9][10] This technique has several advantages in metabolomic studies, as it permits plant genotypes to be differentiated such as genetically modified organisms, 11 different phenotypes, 12,13 and chemotaxonomy identification. 4,14,15 HR-MAS NMR is also widely used for quality control, such as determining the purity, authenticity, and origin of several plant-based products. 16 Additionally, identifying compounds in complex samples is important for the raw-material authentication and origin certification used as phytotherapeutics.…”
Section: Introductionmentioning
confidence: 99%